Dinamika Ketoprak Tobong dalam Novel Panggung Karya Ari Purnomo: Kajian Sosioantropologi Sastra - Umi Kuntari; Mulyana; Dyah Kurnia, Ermi (Sutasoma : Jurnal Sastra Jawa, 2024)
Ketoprak tobong has a long dynamic history from its first appearance to its heyday until it mutated into a modern form. A novel entitled Panggung is a literary work that attempts to portray the history of ketoprak along with the lives of the actors. This study aims to reveal the dynamics of ketoprak tobong, which was once successful and then declined but ultimately still exists. Ketoprak continues to exist because it is willing to transform. The story presented in the novel entitled Panggung is a description of the life experiences of the author, namely Ari Purnomo, who was born and lives in the ketoprak environment. This was a descriptive qualitative study with a socio-anthropological approach to literature. The study results involved: (1) the dynamics of ketoprak from Tobong to a modern form as depicted in the novel; (2) an overview of the causes of the decline of the ketoprak tobong until it was transformed into a modern form based on the story written in the novel entitled Panggung by Ari Purnomo; (3) ketoprak transformation in novel Panggung.